Design of electrical distribution system for industrial plant - Wong, Tee Foo (2017)
Electrical distribution system plays an important role in our daily living, as electrical energy is necessary to run our home and industrial appliances. Consumers demand the delivery of electrical energy to be continuous and seldom to be interrupted, but there is occurrence of breakdown sometimes during the day or night time. Electrical energy is generated by power station, converted from thermal energy into mechanical energy by turbine, and then transformed into electrical energy by generator. The generated electrical energy is transmitted to the load centers via high voltage transmission networks. From the load center (power distribution substation), electrical power supply will be distributed via power transformer to distribution substation and stepped down to lower voltage level for electrical distribution system networks. This research was conducted to evaluate design of electrical distribution system, from 11kV to 400V electrical distribution system up to the final circuits for an upgrading power supply from an existing warehouse building into a manufacturing factory. In this study, aspects determined by follow design procedure for the selection of medium voltage switch gear, type of distribution transformer, low voltage switch board, low voltage components, electrical cable, conductor of its current carrying capacity capability and earth fault protection. The subsequent technical analysis in this dissertation discusses about power factor improvement and relay protection unit that plays an important role in low voltage electrical distribution system. The key finding that the proposed electrical distribution system able to provide adequate, safety, compliances voltage regulation and reliable system and keep it the minimum of interruption electricity power supply.